Anaerobic digestion of cabbage and cauliflower biowaste: Impact of iron oxide nanoparticles (IONPs) on biomethane and microbial communities alteration. (December 2020) - Faisal, Shah; Salama, El-Sayed; Malik, Kamran; Lee, Sang-hun; Li, Xiangkai
Abstract: Recently, vegetable wastes (VWs) utilization received much attention in anaerobic digestion for biomethane production due to its high availability. However, still efforts are needed to improve the VWs digestibility and understand the microbial communities involved in VWs degradation. In this study, iron oxide nanoparticles (IONPs) were synthesized and used in different dosages to systematically evaluate its effect on the digestion of cabbage (CB) and cauliflower leaves (CL). The morphology and particle size of synthesized IONPs were characterized by UV-VIS spectroscopy, FTIR, SEM/EDX, TEM, and XRD. The biomethane production was enhanced by 123% and 79% for CB at 40 mg/L and 60 mg/L IONPs while it was 138% and 106% for CL, respectively. Syntrophomonas, Clostridium, and Methanosarcina were significantly enhanced to 143%, 124%, and 81.55% upon the addition of 40 mg/L IONPs, respectively. Adding IONPs to VWs digestion offers a potential approach to promote key microbial communities and boost biomethane. Graphical abstract: Unlabelled Image Highlights: Synthesized IONPs supported the vegetable biowaste digestion. Biomethane enhanced by 138% and 123% with 40 mg/L IONPs addition. IONPs stimulated the acetogenic bacteria and methanogenic archaea. Major bacterial genera were Syntrophomonas, Clostridium, and Sedimentibacter . Methanosarcina archaea increased to 81.55% in the presence of 40 mg/L IONPs.